Low platelet counts and low CD4/CD8 ratios at apheresis increase the risk of CAR T-cell manufacturing failure in myeloma - Jo, Tomoyasu; Yoshihara, Kyoko; Ri, Masaki; Tsukada, Nobuhiro; Mimura, Naoya; Fujii, Keiko; Fukushima, Kentaro; Fujiwara, Shin-Ichiro; Shimura, Yuji; Haraguchi, Kyoko; Kato, Koji; Satake, Atsushi; et al. (Blood neoplasia, 2025)
•Low platelet counts and low CD4/CD8 T-cell ratios at apheresis increase the risk of CAR T-cell manufacturing failure in multiple myeloma.•Alkylating agents within 6 months before apheresis were associated with decreased platelet counts and CD4/CD8 ratios at apheresis. [Display omitted] Chimeric antigen receptor (CAR) T-cell (CAR-T) therapy has significantly improved management of relapsed or refractory multiple myeloma. However, manufacturing failure due to poor cell growth necessitates revision of treatment strategies that negatively impact patients. To identify risk factors for CAR-T manufacturing failure in patients with myeloma, a nationwide cohort study was performed, analyzing patients who underwent apheresis for idecabtagene vicleucel in Japan. Of 154 patients analyzed, 13 cases (8.4%) experienced manufacturing failure. We compared clinical factors between patients with manufacturing failure (failed group) and those who met specifications (successful group). Patients in the failed group had a higher prevalence of deletion 17p at diagnosis (38.5% vs 14.9%), were more likely to have been treated with alkylating agents within 6 months before apheresis (53.8% vs 23.4%), and had undergone more chemotherapy lines before apheresis (median, 6 vs 5). Additionally, patients with manufacturing failure exhibited significantly lower hemoglobin levels (8.6 vs 10.0 g/dL), platelet counts (5.9 × 104/μL vs 13.8 × 104/μL), and CD4/CD8 ratios (0.169 vs 0.474) than patient with successful manufacturing. Multivariate analysis revealed that low platelet counts (odds ratio [OR], 0.130 for every increase of 105/μL; P = .041), or low CD4/CD8 ratios (OR, 0.100 for each doubling; P = .003) at apheresis increased the risk of manufacturing failure. Alkylating agents within 6 months before apheresis were associated with decreased platelet counts and CD4/CD8 ratios. Manufacturing failure remains an obstacle to CAR-T therapy for patients with myeloma. Avoiding risk factors, such as alkylating agents, and adopting risk-adapted strategies may optimize CAR-T therapy for patients with myeloma.